Estudio de factibilidad para la tercerización de los servicios de recubrimientos duros de piezas industriales, en el municipio de Santiago de Cali, Valle del Cauca. (2013)
This document feasibility will be discussed comprehensively the steps to outsource the service of hard coatings Colombia. The research exercise is necessary to reveal different variables that could affect the course of an event, so that in this way can be recognized in the form of impact the market for this research, a methodology that provides an opportunity for the industry designed of the municipality of Santiago de Cali, to access the hard titanium coating, through a company operating as outsourcing sector. This document consists of a series of sections that will recognize the viability of the project, All are based on a draft proposal , which preliminarily some research objectives , marking the depth of information and the goals to pursue , are reflected in the information contained in Chapters 1 to 11 were made. Potential customers, competitors and potential suppliers, which allow advance contemplate the panorama of the draft Second, a study of the sector, which analyze different characteristics, such as growth, trends, economic and demographic factors was developed. Also, a proposed marketing plan laying the groundwork for the implementation of the project, from advertising and media present. This information will be located in Chapter 12. Chapter 13, 14 and 15 include technical analysis, production plan and management analysis within these product characteristics described marketing and process steps in these chapters detailing graphically the flow of activity, looking for easy recognition by the reader, as well as the organizational structure of the future company. It also includes the physical, human and legal requirements for establishing the project. Finally, Chapter 16 presents the results of the financial analysis, demonstrating the viability of the business and its projection of future sales.